1999
DOI: 10.1164/ajrccm.160.1.9809046
|View full text |Cite
|
Sign up to set email alerts
|

A Dose-dependent Effect of the Novel Inhaled Corticosteroid Ciclesonide on Airway Responsiveness to Adenosine-5 ′ -Monophosphate in Asthmatic Patients

Abstract: Inhaled corticosteroids decrease airway responsiveness in asthma partly through suppression of airway inflammation. We have previously demonstrated that inhaled budesonide reduced airway responsiveness to the mast cell stimulus adenosine-5'-monophosphate (AMP) to a threefold greater extent than to methacholine and sodium metabisulfite, suggesting that AMP responsiveness may be a more sensitive marker of airway inflammation and steroid action in order to assess a dose-response relationship. To investigate this,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
2
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(82 citation statements)
references
References 19 publications
4
75
2
1
Order By: Relevance
“…We performed our challenges in the morning when the airway exhibits enhanced diurnal hyper-responsiveness, so as to coincide with trough protection at the end of the 24-h dosing interval with CIC. Previous data with twice daily CIC have shown a doseresponse against adenosine monophosphate challenge with doses of 100, 400 and 1600 mg daily given each for 2 weeks [21]. In summary, our results showed no significant difference between HFA formulations of once daily CIC 400 mg and twice daily FP 250 mg over 4 weeks for effects on the primary outcome of methacholine hyperresponsiveness in mild-to-moderate asthma.…”
Section: Discussionsupporting
confidence: 47%
“…We performed our challenges in the morning when the airway exhibits enhanced diurnal hyper-responsiveness, so as to coincide with trough protection at the end of the 24-h dosing interval with CIC. Previous data with twice daily CIC have shown a doseresponse against adenosine monophosphate challenge with doses of 100, 400 and 1600 mg daily given each for 2 weeks [21]. In summary, our results showed no significant difference between HFA formulations of once daily CIC 400 mg and twice daily FP 250 mg over 4 weeks for effects on the primary outcome of methacholine hyperresponsiveness in mild-to-moderate asthma.…”
Section: Discussionsupporting
confidence: 47%
“…To date, the dose-dependent effect of ICS on airway eosinophilia has mainly been assessed on induced sputum samples. These studies also indicate that ICS are effective, from low doses onwards, at reducing eosinophil number, and that the dose-response curve is relatively flat [17][18][19][20]. To what extent this is paralleled by changes in mucosal eosinophil number has not been fully established in humans.…”
Section: Discussionmentioning
confidence: 94%
“…The first clinical data on ciclesonide have already been published and have demonstrated that ciclesonide reduces airway responsiveness to adenosine-5Ј-monophosphate in a dose-dependent manner when compared with placebo in patients with mildto-moderate asthma. A reduction in eosinophils was also observed in induced sputum from the same patients (Taylor et al, 1999). Another study has shown that ciclesonide produces a significant inhibition of early and late phase reaction after allergen challenge (Dahl et al, 1998).…”
mentioning
confidence: 75%